The Solution of Diophantine Equation 1^3u_1+1^3u_2+...+k^3u_k=1 - Saethao, Laddawan; Muangkarn, Patchara; Suanoom, Cholatis (Journal of Science and Technology CRRU, 2024)
In this paper, we describe solutions of the Diophantine equation on the following from: where are integers. For our result, we obtain that the equation has one solution if three solution if and at least four general solutions if . Moreover, there is a clear step-by-step method of proof following a mathematical process.